Optimización del Proceso de Extracción por Fluidos Supercríticos en la Obtención de Aceite de Semillas de Uva con el Empleo de la Metodología Taguchi y Superficie de Respuesta - Obregón Tinoco, Henry (2018)
The present work is focused on the revalorization of waste materials from the wine industry such as grape seed for the obtaining of grape oil using supercritical fluid technology. Malbec grape seed was used as raw material to obtain supercritical grape oil, as a potential value added product for both the pharmaceutical and food industries. An initial stage, the physicochemical characterization of the raw material was performed and the results obtained were: humidity (11.4%), proteins (8.1%), ashes (2.5%), fats (11.5%) and carbohydrates (66.5%). In the second stage, preliminary extraction tests with supercritical fluids were carried out using CO2 as a solvent. The following fixed operating parameters were established: average particle size (522.15 μm), supercritical extraction time in steady state (30 minutes), supercritical extraction time in dynamic state (180 minutes) and CO2 flowrate (5 ft3/h). The results were evaluated in terms of yield (g oil obtained / g raw material x100%). Subsequently, the parameters pressure (psi) an temperature (C) that significantly influenced (p <0.05) in the supercritical oil yield were evaluated using the Orthogonal Array L9 of the Taguchi methodology. The levels established for the pressures were: 2205,4410 and 6615 PSI, and the temperatures were: 40, 50 and 60ºC. The result indicated that both factors were significant and the best values respect to the performance of the supercritical oil were pressure (6615 PSI) and temperature (60ºC). In the next stage, we performed the optimization of the significant factors pressure and temperature by applying the Response Surface Methodology, with a central composite design (4 factorial treatments, 4 axial treatments and 2 central point treatments). The optimal temperature and pressure were 68 °C and 7655 psi with an extraction yield of 8.14 percent. Finally, the physico- chemical characterization of the obtained supercritical oil shows that linoleic and oleic fatty acids were found in highest proportion: 64.9 percent and 21.8 percent, respectively.